Understanding military culture : a Canadian perspective - English, Allan D. (Allan Douglas), 1949- (McGill-Queen's University Press, 2004)
Culture has been described as the "bedrock of military" effectiveness because it influences everything an armed service does. The recent conflicts in Afghanistan and Iraq have highlighted the importance of culture as a concept in analyzing the ability of military organizations to perform certain tasks. In fact, a military's culture may determine its preferred way of fighting and dealing with other challenges, like incorporating new technologies, more than its doctrine or organizational structure. This book examines military culture from a theoretical and a practical point of view. It focuses on the Canadian and American military cultures, and it provides the first detailed examination of the culture of the Canadian Forces. It also compares their culture to that of the US armed forces. The book concludes that while the culture of the Canadian Forces has been "Americanized" to a certain extent, the culture of the US armed forces, due to changes in their personnel and roles, has experienced a certain degree of "Canadianization" at the end of the 20th and the beginning of the 21st centuries.